The consequences of job crafting: a three-wave study. Issue 3 (3rd May 2016) - Vogt, Katharina; Hakanen, Jari J.; Brauchli, Rebecca; Jenny, Gregor J.; Bauer, Georg F.
Abstract : This longitudinal study examined the consequences of job crafting on two important employee outcomes: psychological capital (PsyCap) as a work-related personal resource and work engagement as an indicator of employee well-being. The study also tested the reverse causation effects of PsyCap and work engagement on job crafting. It used a three-wave, three-month panel design to survey 940 employees from three European countries working in a broad range of economic sectors and occupations. The results of the cross-lagged longitudinal structural equation modelling demonstrated that job crafting predicted PsyCap and work engagement over time. No reverse causation effects were found. Overall, this study shows that when individuals proactively build a resourceful and challenging work environment for themselves, it can lead to diverse positive outcomes that are crucial to employee health and well-being. Employees should therefore be encouraged and be given the opportunity to craft their own jobs.